G197(P) A systematic review of quality improvement initiatives in low and middle income countries for hospitalised sick and small neonates. (12th March 2018) - Zaka, N; Alexander, EC; Manikam, L; Norman, I; Akhbari, M; Moxon, S; Ram, PK; Murphy, G; English, M; Niermeyer, S; Pearson, L
Abstract : Aims: 98% of the estimated 2.7 million neonatal deaths in 2015 occurred in low- and middle-income countries (LMICs). Within this group, neonates who are preterm or small for gestational age are at higher risk given the notable incidence of cardiopulmonary and neurodevelopmental disorders, and infectious complications, in this group. Quality Improvement (QI) initiatives can reduce the burden of morbidity and mortality for hospitalised neonates in LMICs. We undertook a systematic review to synthesise evidence from LMICs on QI approaches used, outcome measures employed, and the nature of any barriers or promoters for efficacy. Methods: Database searching included Medline, EMBASE, WHO Global Health Library, Cochrane Library, WHO ICTRP and ClinicalTrials.gov, and we conducted citation searching of identified studies and reviews. Search terms were 'neonates', 'quality improvement', 'hospitalised' and derivatives. Studies were excluded if they took place in high income countries, did not include QI interventions, did not include small/sick hospitalised neonates. Included studies were published between January 2000–April 2017. Quality appraisal was conducted with use of Cochrane Risk of Bias tools for interventions. Results: A total of 28 studies were included, covering 23 LMICs and 57 902 participants. The interventions mostly took place at the district and clinic level, and secondly at the level of patient-provider interaction. Educational interventions were most common, and other popular interventions included service organisation and referencing material dissemination. Mortality was the most commonly assessed outcome, and length of admission, sepsis rates and infection rates were also commonly investigated. Barriers included overburdened staff and insufficient equipment; promoters included motivation of key figures and monitoring. Conclusion: To our knowledge this is the first systematic review to examine QI initiatives in this specific population. The majority of QI initiatives for hospitalised small and sick neonates are aimed at the district and clinic level. Outcomes tended to focus on the delivery of safe and effective care, but rarely focused on people-centred, timely or equitable care. Programme planners should aim for coordinated, larger-scale interventions, sustainable information systems, and to be mindful of barriers.